Revealing the Visual Structure of the 1981 and 2019 Versions of Ratu Ilmu Hitam Film Posters - yuliansyah, hendy (Pascasarjana ISBI Bandung, 2024)
The horror film Queen of Black Magic, which is a remake of the film with the same title, was released in 1981 and 2019. This film was released with the same title, but with different characters. The 1981 version features Suzzanna as the horror queen as the main character, while the 2019 version does not feature Suzzanna and the main character is not famous. This film with the title black magic has become an iconic film, because it emphasizes the word science for horror stories. The word black, which is synonymous with magic, is juxtaposed with the word science, thus forming a paradoxical word relationship. The queen is a figure and incarnation of a ghost, which directly places the ghost in a noble and respected position. The posters for the two films have different designs because of the strength of the ideas, social and cultural atmosphere that exist in the two posters with the large distance between the years of release. This research aims to determine the differences in design concepts between two film poster designs. This analysis is based on Levi Strausss version of structuralism theory which reveals that the 1981 version of the Queen of Black Magic poster emphasizes the importance of Suzzanna as a figure or queen of horror who attracts public attention, while the 2019 version of the Queen of Black Magic poster emphasizes the exploration of the formation of visual elements that lead to the meaning of black magic.